Способы предупреждения развития дефектов элементов конструкций турбогенераторов - Шевченко, Валентина Владимировна (Приазовський державний технічний університет, 2016)
В работе показано, что оценка вероятности возникновения отказов из-за конструкторско-технологических и эксплуатационных недоработок, превышения времени работы турбогенераторов на блоках по статистическим данным неточна и не может быть использована на практике для выявления предаварийных состояний турбогенераторов и их своевременного останова. Выполнен анализ и классификация наиболее часто встречающихся дефектов турбогенераторов, предложены способы оценки их значимости и снижения вероятности развития.

The paper shows that the determination of a failure probability due to the design, technological and operational drawbacks, as well as due to the turbogenerators working time exceeding from statistics data is inaccurate. Machine park of turbogenerators being rather limited in number, the classification and the distribution of generators into groups is random. It can not be used in practice to identify the pre-emergency state of turbogenerators and their timely stop. Analysis and classification of most frequent defects of turbogenerators has been performed. Methods for assessing such defects and reduction of their development have been offered. The article notes that expenses should be taken into account when setting up a monitoring system to assess the state and to identify defects. Reduction of expenditures on both operating and new turbogenerators must be justified. Rapid return of investments must be ensured. The list of additional tests has been proposed: measurement of infrared radiation outside the body of the turbogenerator for the estimation of the thermal field distribution and the defects of gas coolers identification; vibroacoustic inspection of the stator core and casing to find out the defects in the suspension of the core in the stator casing; analysis of the impurities in the cooling gas and in the dry remains of the drainage products to detect the products of the steel core and the winding insulation wear; value measurement and establishment of the partial discharges formation position; research of vibrations to reveal the cracks in the shaft, circuiting in the rotor windings and defects in the bearings. The paper notes that at upgrading as power grows overall and mounting dimensions must be preserved so that the existing foundation could be used as well as the existing security systems. Therefore, when designing or upgrading turbogenerators with an increase in power it is necessary to introduce new design decisions.
Methods to prevent turbogenerators design elements defects
Keywords: турбогенераторы; дефекты; отказ электрооборудования; система охлаждения; turbogenerator; defect; failures of electrical equipment; cooling system